Partnership of the Sociedade Brasileira de Oncologia Pediátrica and International Society of Pediatric Oncology to improve nutritional care for children with cancer in Brazil - Viani,Karina (2017)
Abstract The authors present a proposal of a partnership between the Sociedade Brasileira de Oncologia Pediátrica (SOBOPE) and the International Society of Pediatric Oncology (SIOP) to promote the standardization and improvement of nutritional care of kids under cancer treatment in Brazil. The results of the first meeting in Brazil as well as plans for future meetings are described.